Non Healing Ulcer of Soft Palate: A Common Entity Rarely Seen (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2016)
Oral Tuberculosis is a rare disease, accounting for less than 1% of all cases of tuberculosis. The most common manifestation is a non healing ulcerative lesion of the mucosa which is often misdiagnosed. The recent increase in the incidence of tuberculosis especially after the advent of HIV infection, combined with an emerging global resistance to anti-tuberculous drugs, warrants an increased awareness of the involvement of Mycobacterium tuberculosis in persistent or atypical lesions in oral cavity and oropharynx. Very few cases of oropharyngeal tuberculosis have been described in literature. We report a rare case of tuberculosis of soft palate secondary to pulmonary TB in an 8 year old child.SAARC J TUBER LUNG DIS HIV/AIDS, 2015 XII (2), page : 31-33